COMPARATIVE LIFE CYCLE ASSESSMENT AND TECHNO‑ECONOMIC ANALYSIS OF ETHANOL BLENDS IN GASOLINE AND DIESEL - Muhammad Ahmad Javed; Muhammad Akhtar Tarar; Ayesha Javed; Javed Afzal; Muhammad Talha Javed (Spectrum of Engineering Sciences, 2026)
The transition toward low‑carbon transport fuels has intensified global interest in ethanol blending as an immediately deployable strategy for reducing petroleum dependence, greenhouse gas emissions, and urban air pollution. This study presents a comparative life cycle assessment and techno‑economic analysis of ethanol blends at 10%, 20%, and 30% volumetric substitution levels, hereafter referred to as E10, E20, and E30, in gasoline and diesel applications. The analysis is performed under a cradle-to-grave approach as it includes the cultivation of the feedstock, ethanol production, blending, distribution, combustion, and end use performance. The study is a comparative analysis of 1st generation ethanol pathways (sugarcane molasses, corn) and emerging lignocellulosic ethanol pathways, in particular for South Asia. The techno‑economic component examines the cost of production, retrofits to existing infrastructure, fuel economy impacts, material compatibility, and policy support mechanisms in the presence of different ethanol prices and subsidy policy structures. Results show that ethanol‑gasoline blends can lead to measurable reductions in life-cycle greenhouse gas emissions, particularly when sugarcane- and molasses-based ethanol is produced using efficient cogeneration systems. Ethanol‑diesel emulsions in turn have measurable reductions in particulate matter and smoke with issues regarding phase stability, lubricity, and cetane. While both E20 and E30 offer greater decarbonization potential, they also demand a multi-year program of upgrading the infrastructure, managing fuel quality, and targeted policy support, with E10 being the least disruptive pathway. When ethanol blending is part of a larger policy framework that embraces a sustainability perspective and considers land‑use changes, water-ethanol trade-offs, and rural livelihoods, it can play a significant role in achieving transport decarbonization.